Al-Iqtishad : Jurnal Ilmu Ekonomi Syariah ( Journal of Islamic Economics) - M. Shabri Abd. Madjid (Fakultas Syariah dan Hukum UIN Syahida Jakarta, 2016)
The Short-Run And Long-Run Relationship In Indonesian Islamic Stock Returns M. Shabri Abd. Madjid 1-18 Business Process Reengineering Of Funding On Indonesia’s Islamic Banks Aslam Mei Nur Widigdo, Marimin, Idqan Fahmi, Irfan Syauqi Beik 19-32 Efficiency And Profitability On Indonesian Islamic Banking Industry Muhammad Nadratuzzaman Hosen, Rafika Rahmawati 33-48 Islamic Work Ethics And Audit Opinions: Audit Professionalism And Dysfunctional Behavior As Intervening Variables Tulus Suryanto 49-64 Dual Monetary System And Macroeconomic Performance In Indonesia Sri Herianingrum, Imronjana Syapriatama 65-80 Islamic Business Ethics Implementation In Marketing Communication Of Hajj/Umroh Travel Agency “X” Surabaya Ari Prasetyo, Intan Kusuma Pratiwi 81-100 Risk Of Profit Loss Sharing Financing: The Case Of Indonesia Ernawati 101-116 The Development Of Human Resources In Islamic Financial Industries From Economic And Islamic Financial Graduates Nurul Huda, Nova Rini, Desti Anggraini, Khamim Hudori, Yosi Mardoni 117-136 Application Of Theory Reasoned Action In Intention To Use Islamic Banking In Indonesia Andi Reni, Nor Hayati Ahmad 137-148 Issues And Economic Role Of Waqf In Higher Education Institution: Malaysian Experience Farra Munna Harun, Bayu Taufiq Possumah, M Hakimi Bin Mohd Shafiai, Abd. Halim Mohd. Noor 149-168